Comparison of ََQuality of Life and Treatment Satisfaction among Sample of Iraqi Patients Using Anticoagulant Therapy (Warfarin or Non-Vitamin K Antagonist Oral Anticoagulants) - Al-Metwali, Basma Z.; AL-Ameen, Tuqa M. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Oral anticoagulation medication, warfarin and non-vitamin k antagonist oral anticoagulants (NOAC) may require long term use which may affect patients’ satisfaction with their treatment and their quality of life (QOL). Objective: To compare the quality of life and treatment satisfaction among groups of patients using different anticoagulant therapies (warfarin and NOAC). Patients and methods: A cross-sectional study was performed at Ibn Al-Bitar Hospital for cardiac surgery in Baghdad in the period between December 2022 to May 2023. The study population included a convenient sample of patients receiving either warfarin or non-vitamin k antagonist oral anticoagulants treatment. The Arabic version of the short form 12 (SF-12) questionnaire and the Anti-Coagulant Treatment Satisfaction Scale (ACTS) questionnaire were used to assess the quality of life and satisfaction with treatment respectively. Results: The study included 181 patients in total. The mean physical and mental quality of life scores for study participants were 42.3±9.92 and 52.6±10.36 respectively. There was no significant difference in the QOL between patients taking warfarin and those on non-vitamin k antagonist oral anticoagulants treatment. The mean total satisfaction score was 65.4±6.73. Patients receiving non-vitamin k antagonist oral anticoagulants had significantly higher satisfaction compared to those receiving warfarin (P=0.000). The physical score correlated significantly with gender, educational level, employment status, number of chronic medications and number of chronic diseases. The total satisfaction score correlated significantly with gender, number of chronic medications, number of side effects and duration of anticoagulation. There was a significant correlation between the QOL and treatment satisfaction (P=0.000). Conclusion: Treatment with non-vitamin k antagonist oral anticoagulants showed comparable QOL and higher treatment satisfaction than that of warfarin. Better treatment satisfaction can improve patients’ QOL which may ultimately enhance their adherence to treatment.